New oscillation criteria for third order nonlinear functional differential equations - John Graef; Said Grace; Gokula Chhatria (Electronic Journal of Qualitative Theory of Differential Equations)
The authors consider the general third order functional differential equation \begin{align*} \left(a_{2}(\nu)\left[\left(a_{1}(\nu)\left(x'(\nu)\right)^{\alpha_{1}}\right)'\right]^{\alpha_{2}}\right)'+q(\nu) x^{\beta}(\tau(\nu))=0,\qquad\nu\geq \nu_{0}, \end{align*} and obtain sufficient conditions for the oscillation of all solutions. It is important to note that $\alpha_{i}$ for $i=1,2$, and $\beta$ are somewhat independent of each other. The results obtained are illustrated with examples.